Lithium supplementing method, pre-lithiated negative pole piece, secondary battery and electronic device

By using the lithium supplement method to form a prelithiated negative electrode sheet in lithium-ion batteries, the problems of energy density and cycling performance of the negative electrode materials of existing lithium-ion batteries are solved, and higher energy density and lower cost are achieved.

CN119920842AActive Publication Date: 2025-05-02NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510111741.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials such as graphite materials cannot meet the requirements of energy density. The first Coulombic efficiency of silicon-carbon and silicon-oxygen materials is low and the cycle life is poor, resulting in it not being widely promoted.

Method used

A lithium supplement method is adopted to provide a negative electrode sheet and a lithium supplement composite layer to discharge the process to form a prelithiated negative electrode sheet, thereby improving the first-time Coulomb efficiency and cycle capacity stability of the lithium-ion battery.

Benefits of technology

It improves the first Coulomb efficiency of lithium-ion batteries, reduces cycle capacity attenuation, improves volume energy density, and simplifies battery preparation technology and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920842A_ABST
    Figure CN119920842A_ABST
Patent Text Reader

Abstract

The invention provides a lithium supplementing method, a pre-lithiated negative pole piece, a secondary battery and an electronic device. The lithium supplementing method comprises the following steps: providing the negative pole piece; a lithium supplementing composite layer is provided, the lithium supplementing composite layer comprises a supporting layer, a lithium supplementing layer and an isolating membrane presoaked with electrolyte, and the lithium supplementing layer is arranged between the isolating membrane and the supporting layer. The lithium supplementing composite layer and the negative electrode piece are attached, the isolating membrane makes contact with the negative electrode material layer, the lithium supplementing composite layer and the negative electrode piece are subjected to discharging treatment, the constant-current discharging current of the discharging treatment is 0.1 C to 3 C, and the discharging time is 0.067 h to 2 h. And after the discharging treatment is finished, stripping the lithium supplementing composite layer from the negative pole piece to obtain the pre-lithiated negative pole piece. The lithium supplementing method is adopted to supplement lithium for the negative pole piece to obtain the pre-lithiated negative pole piece, and the pre-lithiated negative pole piece is applied to the secondary battery, so that the first coulombic efficiency of the secondary battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a lithium supplementation method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode graphite materials can no longer meet the requirements for energy density. Although silicon-carbon and silicon-oxygen negative electrode materials have high theoretical specific capacity and are ideal materials for replacing negative electrode graphite materials and improving the energy density of lithium-ion batteries, they have not been widely used due to their low first coulomb efficiency and poor cycle life. The existing method to improve the first coulomb efficiency and reduce cycle attenuation of silicon-carbon or silicon-oxygen negative electrodes is to pre-replenish lithium to the negative electrode plate to supplement the irreversible capacity consumed during the first charge, discharge, and cycle, improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, and then improve the energy density of lithium-ion batteries.

[0003] The existing negative electrode plate lithium replenishment methods mainly include lithium powder replenishment, lithium strip replenishment and electrochemical replenishment. However, the above three lithium replenishment methods have certain problems in environmental control, lithium replenishment uniformity, and side reactions after lithium replenishment. Therefore, it is urgent to provide a pre-lithiated negative electrode plate that can improve the first coulomb efficiency of lithium-ion batteries containing silicon-carbon or silicon-oxygen negative electrodes, reduce cycle capacity attenuation, and improve the energy density of lithium-ion batteries. Summary of the invention

[0004] The purpose of this application is to provide a lithium replenishment method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device to improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the volume energy density of the secondary battery. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a lithium replenishment method, which includes the following steps: providing a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector; providing a lithium replenishment composite layer, the lithium replenishment composite layer including a support layer, a lithium replenishment layer and a separator pre-impregnated with an electrolyte, and the lithium replenishment layer is arranged between the separator and the support layer; laminating the lithium replenishment composite layer and the negative electrode plate, so that the separator is in contact with the negative electrode material layer, and performing a discharge treatment on the lithium replenishment composite layer and the negative electrode plate, wherein the constant current discharge current I of the discharge treatment is 0.1C to 3C, and the discharge time t is 0.067h to 2h; after the discharge treatment is completed, the lithium replenishment composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate. The pre-lithiated negative electrode plate is prepared by the lithium replenishment method of the present application, and the pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the volume energy density of the secondary battery. It can also simplify the preparation process of the secondary battery and reduce the cost.

[0006] In one embodiment of the present application, the negative electrode plate is a gap structure, and the gap structure includes a gap structure along the tape running direction or a gap structure perpendicular to the tape running direction. The negative electrode plate is a gap structure, which can effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery.

[0007] In one embodiment of the present application, when the negative electrode sheet is a gap structure along the running direction, along the thickness direction of the negative electrode sheet, the negative electrode current collector includes a first surface and a second surface relative to each other; the first surface and the second surface are both spaced apart by a negative electrode material layer area and an empty foil area; along the running direction of the negative electrode sheet, the shortest distance D1 between two adjacent negative electrode material layers on the first surface is 5mm to 30mm, and the shortest distance D2 between two adjacent negative electrode material layers on the second surface is 30mm to 150mm. The negative electrode sheet satisfies the above characteristics, which can effectively reduce the thickness of the secondary battery and reduce the amount of negative electrode active material, thereby further improving the volume energy density of the secondary battery and reducing the cost of the secondary battery.

[0008] In one embodiment of the present application, the isolation membrane includes a first isolation membrane, the first isolation membrane and the first surface are arranged oppositely, the first isolation membrane is a gap structure along the running direction, the first isolation membrane includes a base membrane and an isolation membrane coating arranged on at least one surface of the base membrane, the surface of the base membrane is spaced apart by a first region and a second region, the second region is provided with an isolation membrane coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the running direction of the first isolation membrane, the shortest distance D3 between two adjacent first regions in the first isolation membrane is 5mm to 30mm. The first isolation membrane meets the above characteristics, can reduce the possibility of lithium precipitation in the empty foil region, improve the safety performance of the secondary battery, and can also effectively reduce the thickness of the secondary battery, further improving the volume energy density of the secondary battery.

[0009] In one embodiment of the present application, the separator includes a second separator, the second separator and the second surface are arranged oppositely, the second separator is a gap structure along the running direction, the second separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is spaced apart by a first region and a second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the running direction of the second separator, the shortest distance D4 between two adjacent first regions in the second separator is 30 mm to 150 mm. The second separator meets the above characteristics, can reduce the possibility of lithium precipitation in the empty foil region, improve the safety performance of the secondary battery, and can also effectively reduce the thickness of the secondary battery, further improving the volume energy density of the secondary battery.

[0010] In one embodiment of the present application, the separator includes a first separator and a second separator. The first separator and the first surface are arranged oppositely, the first separator is a gap structure along the tape running direction, the first separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is separated by a first region and a second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the tape running direction of the first separator, the shortest distance D3 between two adjacent first regions in the first separator is 5mm to 30mm. The second separator and the second surface are arranged oppositely, the second separator is a gap structure along the tape running direction, the second separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is separated by a first region and a second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the tape running direction of the second separator, the shortest distance D4 between two adjacent first regions in the second separator is 30mm to 150mm. The first isolation film and the second isolation film meet the above characteristics, which can reduce the possibility of lithium deposition in the empty foil area, further improve the safety performance of the secondary battery, and at the same time can effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery.

[0011] In one embodiment of the present application, when the negative electrode sheet is a gap structure perpendicular to the running direction, the surface of the negative electrode current collector is spaced apart by a negative electrode material layer area and an empty foil area; along the running direction perpendicular to the negative electrode sheet, the shortest distance D5 between two adjacent negative electrode material layer areas on the surface of any negative electrode current collector is 5 mm to 150 mm. The negative electrode sheet meets the above characteristics, which can reduce the amount of negative electrode active material and reduce the cost of the secondary battery; after the negative electrode sheet is die-cut, the empty foil area can be used as a pole ear area, which reduces the impedance of the secondary battery, improves the dynamic performance of the secondary battery, and increases the capacity of the secondary battery.

[0012] In one embodiment of the present application, the separator includes a third separator, the third separator is a gap structure along a direction perpendicular to the tape running direction, the third separator includes a base film and a separator coating disposed on at least one surface of the base film, the surface of the base film is spaced apart by a first region and a second region, the second region is provided with a separator coating, the first region is disposed opposite to the negative electrode material layer region, and the second region is disposed opposite to the empty foil region; along the tape running direction perpendicular to the third separator, the shortest distance D6 between two adjacent first regions on the surface of any base film is 5 mm to 150 mm. The third separator meets the above characteristics, can reduce the possibility of lithium deposition in the empty foil region, and improve the safety performance of the secondary battery.

[0013] In one embodiment of the present application, the ionic conductivity σ1 of the separator in the first region is 0.1 mS / cm to 5 mS / cm. By regulating the ionic conductivity of the separator in the first region within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0014] In one embodiment of the present application, the porosity P1 of the separator in the first region is 30% to 45%. By adjusting the porosity of the separator in the first region within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0015] In one embodiment of the present application, the air permeability G of the separator in the first region is 6s / 100mL to 9s / 100mL. By regulating the air permeability of the separator in the first region within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0016] In one embodiment of the present application, the ionic conductivity σ2 of the separator in the second region is 0 mS / cm to 0.1 mS / cm. By regulating the ionic conductivity of the separator in the second region within the above range, the replenishment of lithium in the empty foil region can be effectively reduced, the possibility of lithium precipitation in the empty foil region can be reduced, and the safety performance of the secondary battery can be improved.

[0017] In one embodiment of the present application, the porosity P2 of the separator in the second region is 0 to 1%. By regulating the porosity of the separator in the second region within the above range, the lithium replenishment to the empty foil region can be effectively reduced, the possibility of lithium precipitation in the empty foil region can be reduced, and the safety performance of the secondary battery can be improved.

[0018] In one embodiment of the present application, the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode plate is 0.1 MPa to 0.6 MPa. The lithium-replenishing composite layer and the negative electrode plate are laminated, and the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode plate is adjusted within the above range during lamination, which can further improve the initial coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery.

[0019] In one embodiment of the present application, the temperature T of the discharge treatment is 25° C. to 90° C. By regulating the temperature of the discharge treatment within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0020] In one embodiment of the present application, the surface density CW of the electrolyte on the separator pre-impregnated with the electrolyte is 3 g / mm 2 Up to 60g / mm 2 Preferably, the surface density CW of the electrolyte on the separator pre-impregnated with electrolyte is 5 g / mm 2 Up to 30g / mm 2 By regulating the surface density of the electrolyte on the separator pre-impregnated with the electrolyte within the above range, it is beneficial to quickly and appropriately replenish lithium in the negative electrode material layer area, and can reduce the possibility of lithium precipitation in the empty foil area, thereby improving the safety performance of the secondary battery.

[0021] In one embodiment of the present application, the thickness H2 of the lithium supplement layer is 0.001 mm to 1 mm, preferably, the thickness H2 of the lithium supplement layer is 0.005 mm to 0.1 mm. By adjusting the thickness of the lithium supplement layer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0022] In one embodiment of the present application, the thickness H3 of the support layer is 3 μm to 50 μm, preferably, the thickness H3 of the support layer is 5 μm to 20 μm. By adjusting the thickness of the support layer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0023] In one embodiment of the present application, the support layer includes at least one of copper foil, nickel foil, steel foil or copper-nickel alloy foil. The above support layer is selected, the support layer is a metal material, has high electronic conductivity, and can achieve electrochemical external short-circuit lithium replenishment; in addition, the support layer can provide better support for the lithium replenishment layer, can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery.

[0024] In one embodiment of the present application, along the running direction of the lithium-replenishing composite layer, the tensile strength K1 of the lithium-replenishing layer (including the supporting layer) is 0.5N / 10mm to 200N / 10mm, preferably, the tensile strength K1 of the lithium-replenishing layer (including the supporting layer) is 1N / 10mm to 100N / 10mm. By adjusting the tensile strength of the lithium-replenishing layer within the above range, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the volume energy density of the secondary battery can be further improved.

[0025] The second aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to the lithium replenishment method in any of the aforementioned embodiments. The pre-lithiated negative electrode sheet is applied to a secondary battery, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the volume energy density of the secondary battery. It can also simplify the preparation process of the secondary battery and reduce the cost.

[0026] The third aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher volume energy density, and the preparation process of the secondary battery is relatively simple and the cost is low.

[0027] The fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher volume energy density.

[0028] Beneficial effects of this application:

[0029] The present application provides a lithium replenishment method, a pre-lithiated negative electrode plate, a secondary battery and an electronic device, wherein the lithium replenishment method comprises the following steps: providing a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. Providing a lithium replenishment composite layer, the lithium replenishment composite layer comprising a support layer, a lithium replenishment layer and an isolation membrane pre-impregnated with an electrolyte, wherein the lithium replenishment layer is disposed between the isolation membrane and the support layer. The lithium replenishment composite layer and the negative electrode plate are laminated so that the isolation membrane contacts the negative electrode material layer, and the lithium replenishment composite layer and the negative electrode plate are subjected to a discharge treatment, wherein the constant current discharge current I of the discharge treatment is 0.1C to 3C, and the discharge time t is 0.067h to 2h. After the discharge treatment is completed, the lithium replenishment composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate. The above-mentioned lithium replenishment method is used to replenish lithium for the negative electrode plate to obtain a pre-lithiated negative electrode plate. The pre-lithiated negative electrode plate is applied to a secondary battery, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the volume energy density of the secondary battery.

[0030] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0032] Figure 1 A schematic diagram of the structure of a negative electrode plate during lithium replenishment in one embodiment of the present application;

[0033] Figure 2 A schematic diagram of the structure of a negative electrode sheet according to an embodiment of the present application;

[0034] Figure 3 A schematic diagram of the structure of a negative electrode sheet according to another embodiment of the present application;

[0035] Figure 4 A schematic structural diagram of a first isolation membrane according to an embodiment of the present application;

[0036] Figure 5 A schematic diagram of the structure of a second isolation membrane according to an embodiment of the present application;

[0037] Figure 6 A schematic diagram of the structure of a negative electrode sheet according to another embodiment of the present application;

[0038] Figure 7 It is a schematic structural diagram of a third isolation membrane according to an embodiment of the present application. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0040] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0041] The first aspect of the present application provides a lithium replenishment method, which includes the following steps: (1) providing a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. It can be understood that the above-mentioned negative electrode plate refers to a negative electrode plate that has not been pre-lithiated. (2) providing a lithium replenishment composite layer, the lithium replenishment composite layer including a support layer, a lithium replenishment layer and an isolation membrane pre-impregnated with an electrolyte, and the lithium replenishment layer is arranged between the isolation membrane and the support layer. (3) laminating the lithium replenishment composite layer and the negative electrode plate so that the isolation membrane contacts the negative electrode material layer, and performing a discharge treatment on the lithium replenishment composite layer and the negative electrode plate, wherein the constant current discharge current I of the discharge treatment is 0.1C to 3C, and the discharge time t is 0.067h to 2h. (4) after the discharge treatment is completed, the lithium replenishment composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate.

[0042] Illustratively, I can be 0.1C, 0.3C, 0.5C, 0.9C, 1C, 1.3C, 1.5C, 1.9C, 2C, 2.3C, 2.5C, 2.9C, 3C, or a range consisting of any two of the above values; the value of t can be 0.067, 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.1, 1.3, 1.5, 1.7, 1.9, 2, or a range consisting of any two of the above values.

[0043] In step (1), the negative electrode plate can be dried until the water content is ≤500ppm. The negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application is not particularly limited as long as the purpose of this application can be achieved.

[0044] In the present application, the negative electrode material layer includes a negative electrode active material. The negative electrode active material includes at least one of a graphite material, hard carbon, a silicon-carbon material or a silicon-oxygen material. The above-mentioned graphite material includes at least one of artificial graphite or natural graphite. In the present application, the silicon-carbon material is a silicon-carbon composite material, and based on the mass of the silicon-carbon composite material, the mass percentage of the silicon element is 30% to 70%, and the mass percentage of the carbon element is 30% to 70%. The present application has no particular restrictions on the silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be a silicon material deposited on a carbon skeleton, or a carbon material deposited on a silicon skeleton. The silicon-oxygen material includes SiOx, wherein 0<x<2. Exemplarily, the silicon-oxygen material can include silicon oxide (SiO, the molar ratio of silicon to oxygen is 1:1). The negative electrode material layer also includes a negative electrode binder and a negative electrode conductor. The present application has no particular restrictions on the type of negative electrode binder, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include at least one of polyacrylate, polyimide, polyamide, polyamideimide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application has no particular restrictions on the type of negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include but is not limited to at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes or few-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to at least one of vapor-grown carbon fibers (VGCF) or nanocarbon fibers. The above-mentioned metal material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent in the negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.

[0045] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector (such as lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.). The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 20μm. The present application has no particular restrictions on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30μm to 250μm.

[0046] In the present application, in step (3), the lithium supplement composite layer and the negative electrode plate are laminated so that the separator is in contact with the negative electrode material layer. Figure 1 As shown, for ease of understanding, the thickness direction of the negative electrode sheet and the lithium supplement composite layer is defined as the Z direction. The negative electrode sheet includes a negative electrode current collector 14 and a negative electrode material layer 15 arranged on both surfaces of the negative electrode current collector 14. The lithium supplement composite layer 10 includes a support layer 11, a lithium supplement layer 12 and a separator 13 pre-impregnated with an electrolyte. The lithium supplement layer 12 is arranged between the separator 13 pre-impregnated with an electrolyte and the support layer 11. The lithium supplement composite layer 10 and the negative electrode sheet are laminated so that the separator 13 is in contact with the negative electrode material 15 layer. It can be understood that the above-mentioned negative electrode sheet refers to a negative electrode sheet that has not been pre-lithiated.

[0047] In the present application, the lithium replenishment composite layer and the negative electrode plate are discharged through a voltage control system, wherein the positive electrode of the voltage control system is connected to the negative electrode plate, and the negative electrode of the voltage control system is connected to the lithium replenishment layer. During the above-mentioned discharge treatment, the potential of the negative electrode plate is higher than that of the lithium replenishment layer. The negative electrode plate serves as the "positive electrode" and the lithium replenishment layer serves as the "negative electrode". Therefore, if the lithium replenishment of the negative electrode plate is to be achieved and the lithium ions are transferred from the lithium replenishment layer to the negative electrode plate, a discharge treatment is required.

[0048] The present application has no particular restrictions on the environmental parameters during the lithium supplementation process, as long as the purpose of the present application can be achieved. For example, the environmental parameters of step (1) can be temperature ≤ 30°C and humidity ≤ 1.7%, the environmental parameters of step (2) can be temperature ≤ 30°C and humidity ≤ 1.7%, the environmental parameters of step (3) can be humidity ≤ 1.7%, and the environmental parameters of step (4) can be temperature ≤ 30°C and humidity ≤ 1.7%.

[0049] The inventors have found that by using the lithium replenishment method provided in the present application to replenish lithium on the negative electrode plate, the lithium replenishment layer and the negative electrode material layer can form an electrochemical external short circuit, the lithium atoms in the lithium replenishment layer undergo an oxidation reaction to lose electrons to generate lithium ions, the lithium ions are transmitted to the surface or the inside of the negative electrode material layer through the isolation membrane pre-impregnated with the electrolyte, the electrons are transmitted to the negative electrode current collector through the external circuit and then to the surface or the inside of the negative electrode material layer, the electrons and the lithium ions undergo a reduction reaction in the negative electrode material layer to form a lithium intercalation compound, thereby achieving pre-lithiation of the negative electrode material layer, so as to replenish the active lithium lost due to the formation of a solid electrolyte interface (SEI) film during the initial charging and discharging process of the secondary battery. and active lithium lost in the cycle process; and by regulating the conditions of the discharge treatment, a relatively dense and stable SEI film can be formed on the surface of the negative electrode plate, reducing the probability of the negative electrode active material being destroyed due to the co-embedding of solvent molecules, improving the transmission efficiency of lithium ions, and reducing the side reactions between the negative electrode plate and the electrolyte. At the same time, since a relatively dense and stable SEI film is formed in the above-mentioned discharge treatment process, the formation step can be omitted in the subsequent preparation process of the secondary battery, reducing the consumption of the electrolyte in the formation process, and increasing the overall electrolyte retention in the secondary battery; further, omitting the formation step can also improve the production efficiency of the secondary battery and reduce the cost. In addition, since the negative electrode plate is replenished with lithium by means of an electrochemical external short circuit, an isolation membrane pre-impregnated with electrolyte is provided between the negative electrode material layer and the lithium replenishment layer. The isolation membrane has good ion conductivity, which can reduce the probability of the lithium replenishment layer adhering to the surface of the negative electrode material layer, reduce the impact of the side reactions that may occur in the negative electrode material layer due to the high activity of lithium metal in the lithium replenishment layer on the electrochemical performance of the secondary battery, and can also reduce the impact of the silicone oil residue on the surface of the lithium replenishment layer on the surface of the negative electrode material layer entering the secondary battery on the electrochemical performance of the secondary battery. Therefore, the pre-lithiated negative electrode plate is prepared by the lithium replenishment method of the present application, and the pre-lithiated negative electrode plate is applied to the secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the volume energy density of the secondary battery. It can also simplify the preparation process of the secondary battery and reduce the cost.

[0050] In one embodiment of the present application, the negative electrode sheet is a continuous structure. The above-mentioned continuous structure refers to the continuous arrangement of the negative electrode material layer on the surface of the negative electrode current collector. Figure 2 As shown, the negative electrode material layer 15 on the surface of the negative electrode current collector 14 is continuously arranged. Compared with the gap structure, the two layers of negative electrode material layers at the end of the continuous structure do not play the capacity, and at the same time occupy the thickness, resulting in a relatively low volume energy density of the secondary battery. The negative electrode plate is a continuous structure, and the lithium replenishment method of the present application is used to replenish lithium on the above-mentioned negative electrode plate, which can improve the first coulomb efficiency of the secondary battery and reduce the cycle capacity attenuation.

[0051] In one embodiment of the present application, the isolation membrane is a continuous structure, and the ionic conductivity σ3 of the isolation membrane is 0.1 mS / cm to 5 mS / cm. For example, the value of σ3 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or a range consisting of any two of the above values; and / or, the porosity P3 of the isolation membrane is 30% to 45%. For example, the value of P3 can be 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45%, or a range consisting of any two of the above values. and / or, the air permeability G1 of the separator is 6s / 100mL to 9s / 100mL. For example, G1 can be 6s / 100mL, 6.3s / 100mL, 6.6s / 100mL, 6.9s / 100mL, 7s / 100mL, 7.3s / 100mL, 7.6s / 100mL, 7.9s / 100mL, 8s / 100mL, 8.3s / 100mL, 8.6s / 100mL, 8.9s / 100mL, 9s / 100mL, or a range consisting of any two of the above values. It can be understood that when the negative electrode sheet is a continuous structure, the separator also corresponds to a continuous structure.

[0052] In one embodiment of the present application, the negative electrode pole piece is a gap structure, and the gap structure includes a gap structure along the running direction or a gap structure perpendicular to the running direction. In the present application, the running direction is also the MD direction, that is, the length direction; the direction perpendicular to the running direction is also the TD direction, that is, the width direction. The above-mentioned gap structure refers to the spacing of the negative electrode material layers on the surface of the negative electrode current collector, and there is an empty foil area between two adjacent negative electrode material layers. The negative electrode pole piece is a gap structure, which can effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery; at the same time, the lithium replenishment method of the present application is used to replenish the above-mentioned negative electrode pole piece with lithium, which can improve the first coulomb efficiency of the secondary battery and reduce the cycle capacity attenuation.

[0053] In one embodiment of the present application, Figure 3As shown, when the negative electrode plate is a gap structure along the running direction, along the thickness direction of the negative electrode plate, that is, the Z direction, the negative electrode current collector 14 includes a first surface 141 and a second surface 142 relative to each other; the first surface 141 and the second surface 142 are both spaced apart from each other by negative electrode material layer areas and empty foil areas; along the running direction of the negative electrode plate, that is, the X direction, the shortest distance D1 between two adjacent negative electrode material layer areas of the first surface 141 is 5 mm to 30 mm, and the shortest distance D2 between two adjacent negative electrode material layer areas of the second surface 142 is 30 mm to 150 mm. Exemplarily, the value of D1 can be 5, 7, 9, 10, 13, 15, 17, 20, 23, 25, 27, 30 or a range consisting of any two of the above values; the value of D2 can be 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 or a range consisting of any two of the above values. In one embodiment of the present application, D1 < D2. The negative electrode sheet meets the above characteristics, which can effectively reduce the thickness of the secondary battery and reduce the amount of negative electrode active material, thereby further improving the volume energy density of the secondary battery and reducing the cost of the secondary battery. It can be understood that the size of the negative electrode material layer area along the X direction is the length of the negative electrode material layer area. In the present application, the length of a single negative electrode material layer area on the first surface is 180mm to 3000mm; the length of a single negative electrode material layer area on the second surface is 60mm to 2975mm.

[0054] In one embodiment of the present application, the isolation membrane includes a first isolation membrane, the first isolation membrane and the first surface are arranged oppositely, the first isolation membrane is a gap structure along the running direction, the first isolation membrane includes a base membrane and an isolation membrane coating arranged on at least one surface of the base membrane, the surface of the base membrane is spaced apart from the first region and the second region, the second region is provided with an isolation membrane coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the running direction of the first isolation membrane, the shortest distance D3 between two adjacent first regions in the first isolation membrane is 5 mm to 30 mm. Exemplarily, the value of D3 can be 5, 7, 9, 10, 13, 15, 17, 20, 23, 25, 27, 30 or a range consisting of any two of the above values. In the present application, "the first isolation membrane is a gap structure along the running direction" means that the isolation membrane coating on the surface of the base membrane in the first isolation membrane is arranged at intervals. The negative electrode plate is a gap structure along the running direction, and the first isolation membrane also corresponds to a gap structure along the running direction. The first isolation membrane meets the above characteristics, which can reduce the possibility of lithium precipitation in the empty foil area and improve the safety performance of the secondary battery. At the same time, it can also effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery. It can be understood that the size of the first area along the X direction is the length of the first area. In the present application, the length of a single first area in the first isolation membrane is 180mm to 3000mm. Specifically, Figure 4 As shown, the first isolation membrane is a gap structure along the running direction, the first isolation membrane includes a base membrane 21 and an isolation membrane coating arranged on two surfaces of the base membrane 21, the two surfaces of the base membrane 21 are spaced apart by a first region and a second region, the second region is provided with an isolation membrane coating, the first region is arranged opposite to the negative electrode material layer region, and the second region is arranged opposite to the empty foil region; along the running direction of the first isolation membrane, that is, the X direction, the shortest distance D3 between two adjacent first regions in the first isolation membrane is 5 mm to 30 mm.

[0055] In one embodiment of the present application, the separator includes a second separator, the second separator and the second surface are arranged oppositely, the second separator is a gap structure along the running direction, the second separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is spaced apart from the first region and the second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the running direction of the second separator, the shortest distance D4 between two adjacent first regions in the second separator is 30 mm to 150 mm. Exemplarily, the value of D4 can be 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 or a range consisting of any two of the above values. In the present application, "the second separator is a gap structure along the running direction" means that the separator coating on the surface of the base film in the second separator is arranged at intervals. The negative electrode plate is a gap structure along the tape direction, and the second isolation membrane is also a gap structure along the tape direction. The second isolation membrane meets the above characteristics, which can reduce the possibility of lithium precipitation in the empty foil area and improve the safety performance of the secondary battery. At the same time, it can also effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery. In this application, the length of a single first area in the second isolation membrane is 60mm to 2975mm. Specifically, Figure 5 As shown, the second separator is a gap structure along the running direction, the second separator includes a base film 21 and a separator coating disposed on two surfaces of the base film 21, the first region and the second region are arranged at intervals on both surfaces of the base film 21, the second region is provided with a separator coating, the first region is arranged opposite to the negative electrode material layer region, and the second region is arranged opposite to the empty foil region; along the running direction of the second separator, that is, the X direction, the shortest distance D4 between two adjacent first regions in the second separator is 30 mm to 150 mm. In one embodiment of the present application, D3<D4.

[0056] In one embodiment of the present application, the separator includes a first separator and a second separator. The first separator and the first surface are arranged oppositely, the first separator is a gap structure along the tape running direction, the first separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is separated by a first region and a second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the tape running direction of the first separator, the shortest distance D3 between two adjacent first regions in the first separator is 5mm to 30mm. The second separator and the second surface are arranged oppositely, the second separator is a gap structure along the tape running direction, the second separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is separated by a first region and a second region, the second region is provided with a separator coating, the first region is arranged oppositely to the negative electrode material layer region, and the second region is arranged oppositely to the empty foil region; along the tape running direction of the second separator, the shortest distance D4 between two adjacent first regions in the second separator is 30mm to 150mm. The negative electrode plate is a gap structure along the running direction, and the first isolation membrane and the second isolation membrane also correspond to gap structures along the running direction. The first isolation membrane and the second isolation membrane meet the above characteristics, which can reduce the possibility of lithium precipitation in the empty foil area and further improve the safety performance of the secondary battery. At the same time, it can also effectively reduce the thickness of the secondary battery and further improve the volume energy density of the secondary battery.

[0057] In one embodiment of the present application, when the negative electrode sheet is a gap structure perpendicular to the running direction, the surface of the negative electrode collector is spaced apart by a negative electrode material layer area and an empty foil area; along the running direction perpendicular to the negative electrode sheet, the shortest distance D5 between two adjacent negative electrode material layer areas on the surface of any negative electrode collector is 5 mm to 150 mm. Exemplarily, the value of D5 can be 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 or a range consisting of any two of the above values. The negative electrode sheet meets the above characteristics, which can reduce the amount of negative electrode active material and reduce the cost of the secondary battery; after the negative electrode sheet is die-cut, the empty foil area can be used as a pole ear area to reduce the impedance of the secondary battery, improve the dynamic performance of the secondary battery, and increase the capacity of the secondary battery. It can be understood that the size of the negative electrode material layer area along the Y direction is the width of the negative electrode material layer area. In the present application, the width of a single negative electrode material layer is 30 mm to 150 mm. Figure 6 As shown, when the negative electrode plate is a gap structure perpendicular to the running direction, the surface of the negative electrode collector (not shown in the figure) is spaced apart by a negative electrode material layer area 151 and an empty foil area 152; along the running direction perpendicular to the negative electrode plate, that is, the Y direction, the shortest distance D5 between two adjacent negative electrode material layer areas 151 on one surface of the negative electrode collector is 5 mm to 150 mm.

[0058] In one embodiment of the present application, the separator includes a third separator, the third separator is a gap structure along a direction perpendicular to the tape running direction, the third separator includes a base film and a separator coating arranged on at least one surface of the base film, the surface of the base film is spaced apart by a first region and a second region, the second region is provided with a separator coating, the first region is arranged opposite to the negative electrode material layer region, and the second region is arranged opposite to the empty foil region; along the tape running direction perpendicular to the third separator, the shortest distance D6 between two adjacent first regions on the surface of any base film is 5mm to 150mm. Exemplarily, the value of D6 can be 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 or a range consisting of any two of the above values. The negative electrode sheet is a gap structure along a direction perpendicular to the tape running direction, and the third separator also corresponds to a gap structure along a direction perpendicular to the tape running direction, and the third separator meets the above characteristics, which can reduce the possibility of lithium deposition in the empty foil region and improve the safety performance of the secondary battery. It is understood that the size of the first region along the Y direction is the width of the first region. In the present application, the width of a single first region is 30 mm to 150 mm. Specifically, Figure 7 As shown, the third isolation membrane is a gap structure along a direction perpendicular to the tape running direction. The third isolation membrane includes a base membrane (not shown in the figure) and an isolation membrane coating arranged on a surface of the base membrane. The surface of the base membrane is spaced apart by a first region 201 and a second region 202, and the second region 202 is provided with an isolation membrane coating. The first region 201 is arranged opposite to the negative electrode material layer region, and the second region 202 is arranged opposite to the empty foil region. Along the tape running direction perpendicular to the third isolation membrane, that is, the Y direction, the shortest distance D6 between two adjacent first regions 201 on the surface of the base membrane is 5 mm to 150 mm.

[0059] In one embodiment of the present application, the ionic conductivity σ1 of the isolation membrane of the first region is 0.1mS / cm to 5mS / cm. Exemplarily, the value of σ1 can be 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the above values. In the present application, the ionic conductivity of the first isolation membrane, the second isolation membrane, and the third isolation membrane in the first region are all within the above range. The porosity and permeability of the isolation membrane in the first region will affect the ionic conductivity of the isolation membrane in the first region, thereby affecting the constant current discharge current of the lithium replenishment process. By regulating the ionic conductivity of the isolation membrane in the first region within the above range, the electrochemical external short-circuit lithium replenishment process can have a suitable constant current discharge current, which can reduce the possibility of lithium precipitation in the negative electrode material layer; and it is conducive to the rapid and appropriate replenishment of lithium in the negative electrode material layer, which can effectively supplement the active lithium lost due to the formation of the SEI film during the first charge and discharge process of the secondary battery and the active lithium lost during the cycle process, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery. The present application does not particularly limit the method of regulating the ionic conductivity of the isolation membrane in the first region, as long as the purpose of the present application can be achieved. For example, the ionic conductivity of the isolation membrane in the first region can be regulated by regulating the porosity and / or permeability of the isolation membrane in the first region. Exemplarily, the porosity of the isolation membrane in the first region increases, and the ionic conductivity of the isolation membrane in the first region increases; the porosity of the isolation membrane in the first region decreases, and the ionic conductivity of the isolation membrane in the first region decreases. Illustratively, as the air permeability of the isolation membrane in the first region increases, the ionic conductivity of the isolation membrane in the first region increases; as the air permeability of the isolation membrane in the first region decreases, the ionic conductivity of the isolation membrane in the first region decreases.

[0060] In one embodiment of the present application, the porosity P1 of the separator of the first region is 30% to 45%. Exemplarily, the value of P1 can be 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 44%, 45% or a range consisting of any two of the above values. In the present application, the porosity of the first separator, the second separator, and the third separator of the first region are all within the above range. By regulating the porosity of the separator of the first region within the above range, the separator of the first region can have a suitable ionic conductivity, the electrochemical external short-circuit lithium replenishment process can have a suitable constant current discharge current, and the possibility of lithium precipitation in the negative electrode material layer can be reduced; and it is conducive to the rapid and appropriate replenishment of lithium in the negative electrode material layer, which can effectively replenish the active lithium lost by the formation of SEI film during the first charge and discharge process of the secondary battery and the active lithium lost during the cycle process, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery. The present application has no particular restrictions on the method of regulating the porosity of the isolation membrane in the first region, as long as the purpose of the present application can be achieved. For example, the porosity of the isolation membrane in the first region can be regulated by regulating the amount of pore-forming agent added during the preparation of the isolation membrane base film or the stretching force during the preparation of the isolation membrane base film.

[0061] In one embodiment of the present application, the air permeability G of the isolation membrane in the first region is 6s / 100mL to 9s / 100mL. For example, G can be 6s / 100mL, 6.3s / 100mL, 6.6s / 100mL, 6.9s / 100mL, 7s / 100mL, 7.3s / 100mL, 7.6s / 100mL, 7.9s / 100mL, 8s / 100mL, 8.3s / 100mL, 8.6s / 100mL, 8.9s / 100mL, 9s / 100mL, or a range consisting of any two of the above values. In the present application, the air permeabilities of the first isolation membrane, the second isolation membrane, and the third isolation membrane in the first region are all within the above range. By regulating the air permeability of the isolation membrane in the first region within the above range, the isolation membrane in the first region can have a suitable ionic conductivity, the electrochemical external short-circuit lithium replenishment process can have a suitable constant current discharge current, and the possibility of lithium precipitation in the negative electrode material layer can be reduced; and it is beneficial to quickly and appropriately replenish the negative electrode material layer, and can effectively replenish the active lithium lost due to the formation of the SEI film during the first charge and discharge process of the secondary battery and the active lithium lost during the cycle process, and can further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery. The present application does not particularly limit the method of regulating the air permeability of the isolation membrane in the first region, as long as the purpose of the present application can be achieved. For example, the air permeability of the isolation membrane in the first region can be regulated by regulating the amount of pore-forming agent added during the preparation of the isolation membrane base film or the tensile force during the preparation of the isolation membrane base film.

[0062] In one embodiment of the present application, the ionic conductivity σ2 of the separator of the second region is 0mS / cm to 0.1mS / cm. Exemplarily, the value of σ2 can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or a range consisting of any two of the above values. In the present application, the ionic conductivity of the first separator, the second separator, and the third separator of the second region are all within the above range. By regulating the ionic conductivity of the separator of the second region within the above range, the ionic conductivity of the separator of the second region is small, and the lithium ion transmission is more difficult, which can effectively reduce the lithium replenishment of the empty foil area, reduce the possibility of lithium precipitation in the empty foil area, and improve the safety performance of the secondary battery. The present application does not particularly limit the method of regulating the ionic conductivity of the separator of the second region, as long as the purpose of the present application can be achieved. For example, the ionic conductivity of the separator of the second region can be regulated by regulating the porosity of the separator of the second region. Illustratively, as the porosity of the isolation membrane in the second region increases, the ionic conductivity of the isolation membrane in the second region increases; as the porosity of the isolation membrane in the second region decreases, the ionic conductivity of the isolation membrane in the second region decreases.

[0063] In one embodiment of the present application, the porosity P2 of the separator of the second region is 0 to 1%. Exemplarily, the value of P2 can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of the above values. In the present application, the porosity of the first separator, the second separator, and the third separator in the second region are all within the above range. By regulating the porosity of the separator of the second region within the above range, the porosity of the separator of the second region is small, the ion conductivity of the separator of the second region is small, and the lithium ion transmission is more difficult, which can effectively reduce the lithium replenishment of the empty foil area, reduce the possibility of lithium precipitation in the empty foil area, and improve the safety performance of the secondary battery. The present application does not particularly limit the method of regulating the porosity of the separator of the second region, as long as the purpose of the present application can be achieved. For example, the porosity of the separator of the second region can be regulated by regulating the surface density of the separator coating.

[0064] In one embodiment of the present application, the interface pressure p per unit area between the lithium replenishing composite layer and the negative electrode plate is 0.1MPa to 0.6MPa. Exemplarily, the value of p can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or a range consisting of any two of the above values. The lithium replenishing composite layer and the negative electrode plate are bonded together, and the interface pressure per unit area between the lithium replenishing composite layer and the negative electrode plate is regulated within the above range during bonding. The lithium replenishing layer and the isolation membrane of the pre-impregnated electrolyte are closely bonded, the interface impedance is small, the impedance uniformity is high, the lithium replenishing efficiency is high, and the lithium replenishing uniformity is high, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery.

[0065] The present application does not particularly limit the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded, as long as the purpose of the present application can be achieved. For example, the manner in which the lithium-replenishing composite layer and the negative electrode sheet are bonded can be winding into a roll or pressing into a sheet. The present application does not particularly limit the method for regulating the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, when the lithium-replenishing composite layer and the negative electrode sheet are wound into a roll, the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet can be regulated by regulating the winding tension. When other conditions remain unchanged, the winding tension increases, and the interface pressure per unit area increases; the winding tension decreases, and the interface pressure per unit area decreases. For example, when the lithium-replenishing composite layer and the negative electrode sheet are pressed into a sheet, the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode sheet can be regulated by regulating the pressing pressure. When other conditions remain unchanged, the pressing pressure increases, and the interface pressure per unit area increases; the pressing pressure decreases, and the interface pressure per unit area decreases.

[0066] In one embodiment of the present application, the temperature T of the discharge treatment is 25°C to 90°C. Exemplarily, the value of T can be 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90 or a range consisting of any two of the above values. By regulating the temperature of the discharge treatment within the above range, combined with a suitable constant current discharge current during the discharge treatment process, the possibility of lithium ionization in the negative electrode material layer can be reduced; it can also reduce the possibility of electrolyte solvent volatilization, so that the electrolyte has a suitable viscosity, so that the electrolyte has a suitable ionic conductivity, thereby providing a higher lithium replenishment rate and a suitable lithium replenishment amount, which can effectively supplement the active lithium lost by the formation of the SEI film during the first charge and discharge process of the secondary battery and the active lithium lost during the cycle process, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery.

[0067] In one embodiment of the present application, the surface density CW of the electrolyte on the separator pre-impregnated with the electrolyte is 3 g / mm 2 Up to 60g / mm 2 Preferably, the surface density CW of the electrolyte on the separator pre-impregnated with electrolyte is 5 g / mm 2 Up to 30g / mm 2 . Exemplarily, the value of CW can be 3, 5, 7, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60 or a range consisting of any two of the above values. By regulating the surface density of the electrolyte on the separator of the pre-impregnated electrolyte within the above range, the electrolyte on the separator has a suitable surface density, which can make the electrochemical external short-circuit lithium replenishment process have a suitable constant current discharge current, thereby facilitating the rapid and appropriate replenishment of lithium to the negative electrode material layer area, and can reduce the possibility of lithium precipitation in the empty foil area, thereby improving the safety performance of the secondary battery. The present application does not particularly limit the method of regulating the surface density of the electrolyte on the separator of the pre-impregnated electrolyte, as long as the purpose of the present application can be achieved. For example, the surface density of the electrolyte on the separator of the pre-impregnated electrolyte can be regulated by regulating the immersion time of the separator in the electrolyte. Generally, when other conditions remain unchanged, the longer the immersion time of the separator in the electrolyte, the greater the surface density of the electrolyte on the separator pre-impregnated with the electrolyte; the shorter the immersion time of the separator in the electrolyte, the less the surface density of the electrolyte on the separator pre-impregnated with the electrolyte. The type of separator and the composition ratio of the electrolyte usually also affect the surface density of the electrolyte on the separator pre-impregnated with the electrolyte.

[0068] In one embodiment of the present application, the elongation of the isolation membrane under a tensile force of 2N / 10mm to 4N / 10mm is 0 to 1%. For example, the elongation of the isolation membrane under a tensile force of 2N / 10mm to 4N / 10mm can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two of the above values. The isolation membrane that meets the above characteristics has high mechanical strength and is not prone to breakage during the lithium replenishment process, which is conducive to improving the efficiency of lithium replenishment.

[0069] In one embodiment of the present application, the tensile strength of the isolation film along the belt direction is 4000 kg / cm 2 Up to 7000kg / cm 2 , the tensile strength perpendicular to the belt direction is 2000kg / cm 2 Up to 4000kg / cm 2 For example, the tensile strength of the isolation film along the belt running direction can be 4000 kg / cm 2 , 4500kg / cm 2 , 5000kg / cm 2 , 5500kg / cm 2 、6000kg / cm 2 、6500kg / cm 2 , 7000kg / cm 2 Or a range consisting of any two of the above values; the tensile strength of the isolation film perpendicular to the tape direction can be 2000kg / cm 2 , 2500kg / cm 2 、3000kg / cm 2 、3500kg / cm 2 , 4000kg / cm 2 Or it is a range consisting of any two of the above values. The isolation membrane that meets the above characteristics has high mechanical strength and is not prone to breakage during the lithium replenishment process, which is beneficial to improving the lithium replenishment efficiency.

[0070] The separator of the present application can be reused as long as the separator is not damaged after the lithium replenishment is completed. For example, the separator can be reused more than 5 times. The first coulombic efficiency of the pre-lithiated negative electrode sheet prepared by the separator for the first time is a1, and the first coulombic efficiency of the pre-lithiated negative electrode sheet prepared by the ith time is a i , a i / a1 is 99% to 100%, and i is 1 to 15, indicating that the reused isolation membrane has little effect on the first coulombic efficiency of the secondary battery and can be maintained at a high level, which is beneficial to reducing the cost of the preparation process.

[0071] The present application has no particular restrictions on the thickness of the base film, as long as the purpose of the present application can be achieved. For example, the thickness of the base film can be 4μm to 20μm. The present application has no particular restrictions on the material of the base film, as long as the purpose of the present application can be achieved. For example, the material of the base film may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid at least one; the type of base film may include woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane at least one. The present application has no particular restrictions on the thickness of the isolation membrane coating, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation membrane coating can be 3μm to 20μm.

[0072] The present application has no particular restrictions on the electrolyte pre-impregnated in the isolation membrane, as long as the purpose of the present application can be achieved. The above-mentioned electrolyte includes a lithium salt. The present application has no particular restrictions on the type of lithium salt, and lithium salts known in the art can be used. For example, the lithium salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalate borate (LiBF2(C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The above-mentioned electrolyte also includes a non-aqueous organic solvent. The present application has no particular restrictions on the non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propane sultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester. The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.

[0073] In one embodiment of the present application, the lithium supplement layer includes at least one of lithium foil or lithium alloy foil. The lithium alloy foil may include but is not limited to lithium aluminum alloy, lithium magnesium alloy, lithium nickel alloy or lithium silicon alloy.

[0074] In one embodiment of the present application, the thickness H2 of the lithium replenishment layer is 0.001mm to 1mm, and preferably, the thickness H2 of the lithium replenishment layer is 0.005mm to 0.1mm. Exemplarily, the value of H2 can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1 or a range consisting of any two of the above values. By regulating the thickness of the lithium replenishment layer within the above range, the lithium replenishment layer has a suitable thickness, and the lithium replenishment layer can better meet the lithium replenishment demand, which is conducive to further replenishing lithium to the negative electrode plate, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the volume energy density of the secondary battery. In addition, the thickness of the lithium replenishment layer within the above range can also save costs. The present application does not particularly limit the method of regulating the thickness of the lithium replenishment layer, as long as the purpose of the present application can be achieved. For example, the thickness of the lithium replenishing layer can be controlled by adjusting the roller pressure or the calendering force when preparing the lithium replenishing layer.

[0075] In one embodiment of the present application, the thickness H3 of the support layer is 3 μm to 50 μm, preferably, the thickness of the support layer is 5 μm to 20 μm. Exemplarily, the value of H3 can be 3, 4, 5, 7, 9, 10, 13, 15, 17, 19, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values. By regulating the thickness of the support layer within the above range, the support layer has a suitable thickness, which can make the support layer have a higher mechanical strength, can better meet the need of the lithium-replenishing composite layer to be peeled off from the surface of the negative electrode material layer after lithium replenishment, reduce the possibility of fracture of the lithium-replenishing composite layer, and facilitate further lithium replenishment of the negative electrode sheet, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the volume energy density of the secondary battery. In the present application, commercially available support layers of different thicknesses can be selected, and the present application is not particularly limited, as long as the purpose of the present application can be achieved.

[0076] In one embodiment of the present application, the support layer includes at least one of copper foil, nickel foil, steel foil or copper-nickel alloy foil. The above support layer is selected, the support layer is a metal material, has high electronic conductivity, and can achieve electrochemical external short-circuit lithium replenishment; in addition, the support layer can provide better support for the lithium replenishment layer, further improve the mechanical strength of the lithium replenishment composite layer, so that the lithium replenishment composite layer can be more smoothly peeled off from the surface of the negative electrode material layer after lithium replenishment, reduce the possibility of fracture of the lithium replenishment composite layer, and is conducive to further replenishing lithium to the negative electrode plate, thereby further improving the first coulomb efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the volume energy density of the secondary battery.

[0077] In one embodiment of the present application, along the running direction of the lithium-replenishing composite layer, the tensile strength K1 of the lithium-replenishing layer (including the supporting layer) is 0.5N / 10mm to 200N / 10mm, preferably, the tensile strength K1 of the lithium-replenishing layer (including the supporting layer) is 1N / 10mm to 100N / 10mm. Exemplarily, K1 can be 0.5N / 10mm, 1N / 10mm, 10N / 10mm, 20N / 10mm, 30N / 10mm, 40N / 10mm, 50N / 10mm, 60N / 10mm, 70N / 10mm, 80N / 10mm, 90N / 10mm, 100N / 10mm, 150N / 10mm, 200N / 10mm or a range consisting of any two of the above values. By regulating the tensile strength of the lithium replenishment layer within the above range, the lithium replenishment layer has a higher tensile strength and a higher mechanical strength, so that the lithium replenishment composite layer can be more smoothly peeled off from the surface of the negative electrode material layer after lithium replenishment, reducing the possibility of breakage of the lithium replenishment composite layer, which is beneficial to further replenish lithium to the negative electrode plate, thereby further improving the first coulombic efficiency of the secondary battery, further reducing the cycle capacity attenuation, and further improving the volume energy density of the secondary battery.

[0078] The present application has no particular restrictions on the preparation method of the lithium supplement layer, as long as the purpose of the present application can be achieved. For example, under the conditions of ambient temperature ≤30°C and humidity ≤1.7%, a lithium metal powder slurry is coated on the support layer and dried and rolled to form a lithium supplement layer; or lithium foil and / or lithium alloy foil is rolled to the support layer to form a lithium supplement layer; or lithium or lithium alloy molten slurry is coated on the support layer and cooled and rolled to form a lithium supplement layer. The present application has no particular restrictions on the roller pressure of the rolling process in the preparation of the above-mentioned lithium supplement layer, as long as the purpose of the present application can be achieved. For example, the roller pressure p1 can be 0.1T / 10mm to 2T / 10mm. Specifically, the roller pressure p11 of rolling after applying the lithium metal powder slurry to the support layer can be 0.1T / 10mm to 2T / 10mm; the roller pressure p12 of rolling the lithium foil and / or lithium alloy foil to the support layer can be 0.1T / 10mm to 2T / 10mm; the roller pressure p13 of rolling after applying the lithium or lithium alloy molten slurry to the support layer can be 0.1T / 10mm to 2T / 10mm.

[0079] The present application has no particular restrictions on the preparation method of the negative electrode sheet with a gap structure, as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the negative electrode sheet with a gap structure may include the following steps: uniformly mixing the negative electrode active material, the negative electrode conductive agent, the negative electrode binder, and the negative electrode solvent to obtain a negative electrode slurry; using extrusion-type gap coating, gap-coating the negative electrode slurry on one surface of the negative electrode current collector along the belt-feeding direction, drying, and obtaining a negative electrode sheet with a single-sided gap coating of the negative electrode material layer; then repeating the above steps on the other surface of the negative electrode current collector to obtain a negative electrode sheet with a double-sided gap coating of the negative electrode material layer. Exemplarily, a method for preparing a negative electrode sheet with a gap structure may include the following steps: uniformly mixing a negative electrode active material, a negative electrode conductive agent, a negative electrode binder, and a negative electrode solvent to obtain a negative electrode slurry; using extrusion-type gap coating to gap-coat the negative electrode slurry on one surface of a negative electrode collector in a direction perpendicular to the belt running direction, and drying to obtain a negative electrode sheet with a single-sided gap coating of a negative electrode material layer; and then repeating the above steps on the other surface of the negative electrode collector to obtain a negative electrode sheet with a double-sided gap coating of a negative electrode material layer.

[0080] The present application has no particular restrictions on the preparation method of the isolation membrane of the gap structure, as long as the purpose of the present application can be achieved. Exemplarily, the preparation method of the isolation membrane of the gap structure may include the following steps: uniformly mix the polymer, inorganic ceramics, and solvent to obtain the isolation membrane coating slurry, and use extrusion gap coating or gravure gap coating to apply the isolation membrane coating slurry to one surface of the base film along the tape direction (the second area is coated with the isolation membrane coating, and the first area is not coated with the isolation membrane coating), and dry to obtain a single-sided gap-coated isolation membrane; then repeat the above steps on the other surface of the base film to obtain a double-sided gap-coated isolation membrane. Exemplarily, the preparation method of the isolation membrane of the gap structure may include the following steps: uniformly mix the polymer, inorganic ceramics, and solvent to obtain the isolation membrane coating slurry, and use extrusion gap coating or gravure gap coating to apply the isolation membrane coating slurry to one surface of the base film perpendicular to the tape direction (the second area is coated with the isolation membrane coating, and the first area is not coated with the isolation membrane coating), and dry to obtain a single-sided gap-coated isolation membrane; then repeat the above steps on the other surface of the base film to obtain a double-sided gap-coated isolation membrane. The above-mentioned polymers include but are not limited to at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer; the inorganic ceramics include but are not limited to at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate; the solvent includes but is not limited to water or N-methylpyrrolidone (NMP).

[0081] The second aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to the lithium replenishment method in any of the aforementioned embodiments. The pre-lithiated negative electrode sheet is applied to a secondary battery, which can improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity decay, and improve the volume energy density of the secondary battery. It can also simplify the preparation process of the secondary battery and reduce the cost.

[0082] The third aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher volume energy density, and the preparation process of the secondary battery is relatively simple and the cost is low.

[0083] In the present application, the secondary battery also includes a positive electrode plate. The positive electrode plate includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its own thickness direction, or on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive current collector or a partial area of ​​the positive current collector. This application is not particularly limited as long as the purpose of this application can be achieved.

[0084] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).

[0085] The positive electrode material layer of the present application includes a positive electrode active material, and the positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The positive electrode material layer can be one layer or more layers, and each layer in the multi-layer positive electrode material layer can contain the same or different positive electrode active materials. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi 0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3At least one of O2 (NCM111). The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no special restrictions on the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include at least one of the above-mentioned negative electrode conductors; the positive electrode binder may include at least one of the above-mentioned negative electrode binders. The present application has no special restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0086] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 25 μm to 250 μm.

[0087] In the present application, the secondary battery also includes an electrolyte. The present application has no particular restrictions on the electrolyte in the secondary battery, as long as it can achieve the purpose of the present application. For example, the electrolyte in the secondary battery and the electrolyte pre-impregnated with the isolation membrane in the lithium-supplementing composite layer can be the same or different.

[0088] In the present application, the secondary battery also includes a separator. The present application has no particular restrictions on the separator in the secondary battery, as long as the purpose of the present application can be achieved. For example, the separator in the secondary battery and the separator in the lithium supplementation composite layer can be the same or different.

[0089] The secondary battery of the present application also includes a packaging bag for containing a positive electrode plate, a separator, a pre-lithiated negative electrode plate and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0090] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0091] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator, the pre-lithiated negative electrode sheet, and the separator in order, and winding, folding, and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator, the pre-lithiated negative electrode sheet, and the separator in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0092] The fourth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher volume energy density.

[0093] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0094] Example

[0095] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0096] Test methods and equipment:

[0097] Ionic conductivity test of the isolation membrane in the first and second regions:

[0098] (1) Preparation of isolation film samples: Cut the samples to be tested (isolation films in the first area) into the same size (45.3 mm×33.7 mm), bake the samples to be tested at 60° C. for more than 4 h, and then quickly put them into a glove box for later use.

[0099] (2) Preparation of blank symmetrical battery packaging bags: Copper foil (thickness of 14 μm) was used against copper foil (thickness of 14 μm) as the current collector to assemble a blank symmetrical battery packaging bag without a separator. The packaging bag was baked at 60°C for more than 4 h before use, and then quickly placed in a glove box for use.

[0100] (3) Preparation of single-sided negative electrode sheet: Cut the single-sided negative electrode sheet into a size of 23 mm × 38.5 mm, which is used as the electrode for measuring the ionic conductivity of the isolation membrane. After being baked at 105°C in vacuum for more than 4 hours, it is immediately placed in the glove box for use.

[0101] (4) Symmetrical battery assembly: Assemble symmetrical batteries with negative electrode sheets against negative electrode sheets in blank symmetrical battery packaging bags, and assemble different layers (1, 2, 3, 4 layers) of isolation membranes in situ in the middle of the symmetrical electrodes in a glove box to form symmetrical batteries (4 parallel samples of symmetrical batteries with each number of layers are assembled); use a simple packaging machine to seal the sides of the packaging bag, then use a pipette to inject the electrolyte (300 μL), and finally seal the bottom.

[0102] (5) Loading the symmetrical battery into the fixture: Place the packaged symmetrical battery in the glove box overnight to allow the electrolyte to fully infiltrate the isolation membrane.

[0103] (6) Electrochemical impedance spectroscopy (EIS) test: Before measuring EIS, the symmetrical batteries with different numbers of isolation membrane layers were placed in a high and low temperature box at 45°C for half an hour, and the EIS at the set temperature was measured; the EIS test conditions were: the frequency range was set to 1MHz to 1kHz, and the perturbation voltage was set to 5mV. The ionic conductivity σ1 of the isolation membrane in the first region was calculated based on the test results.

[0104] A scatter plot is made of the resistance values ​​obtained from symmetrical batteries with different numbers of isolation membrane layers versus the number of layers n, and then a linear fit is performed. The slope is the resistance k of the isolation membrane. The ionic conductivity σ1 of the isolation membrane in the first region can be calculated according to the following formula.

[0105] The ionic conductivity of the isolation membrane in the first region is σ1=l0 / (k×S); where l0 is the thickness of the single-layer isolation membrane, and S is the effective area of ​​the isolation membrane that can transmit ions when testing impedance, 153.86 mm 2 .

[0106] The composition and preparation method of the electrolyte are the same as those of Example 1-1, and the preparation method of the single-sided negative electrode sheet is as follows:

[0107] Take the negative electrode slurry in Example 1-1, and evenly coat the negative electrode slurry on one surface of a negative electrode current collector copper foil with a thickness of 12 μm, and dry it at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Dry it under vacuum at 90°C for 1 hour, and then cold press it to obtain a single-sided negative electrode sheet. The surface density of the negative electrode material layer is 2.3 mg / cm 2 The compaction density of the cold pressing process is 1.0g / cm 3 .

[0108] (7) Referring to steps (1) to (6), take the isolation membrane of the second region and test the ionic conductivity σ2 of the isolation membrane of the second region.

[0109] Porosity test of the isolation membrane in the first and second regions:

[0110] (1) Sample preparation: Take the isolation film of the first area, wrap it with weighing paper on top and bottom, lay it flat on the die, and punch it with a punching machine to obtain 40 disc samples with a diameter of 16 mm. Test the thickness of the disc samples and take the average value h1.

[0111] (2) Test: Place the 40 disc samples obtained in step (1) into the sample cup of a true density instrument (AccuPyc II1340), tighten the lid, test three times, take the average value of the test results and record it as the true volume V2 of the disc sample, and record the test temperature.

[0112] (3) Result analysis: The apparent volume V1 of the wafer sample = s × h1 × the number of wafer samples, where s is the surface area of ​​the wafer sample and h1 is the thickness of the wafer sample; the porosity of the wafer sample is obtained according to Porosity = (V1-V2) / V1×100%, which is the porosity of the isolation membrane in the first region.

[0113] (4) Referring to steps (1) to (3), take the isolation film of the second region and test the porosity of the isolation film of the second region.

[0114] Air permeability test of the isolation film in the first area:

[0115] (1) Lift and fix the upper cylinder of the air permeability tester (model: Labthink TQD-G1);

[0116] (2) Unscrew the bottom stopcock of the air permeability tester and remove the isolation film (size greater than 6.5 cm) from the first area. 2 Place the rectangular sample) on the bottom disc and tighten the stopcock;

[0117] (3) Gently place the cylinder down, and when the white area on the cylinder passes the sensor, the digital timer will automatically start counting;

[0118] (4) When the white area completely passes through the sensor, the digital timer automatically stops timing and the value on the digital timer is recorded, which is the air permeability of the isolation film in the first area.

[0119] Surface density test of electrolyte on the separator pre-impregnated with electrolyte:

[0120] Before the separator is immersed in the electrolyte, weigh the mass of the separator, recorded as M1 g, and measure the area of ​​the separator, recorded as S mm 2 After the separator is soaked in electrolyte, the mass of the separator is weighed and recorded as M2 g. The surface density of the electrolyte on the separator pre-soaked in electrolyte (g / mm 2 )=(M2-M1) / S.

[0121] Thickness test of lithium supplement layer and support layer:

[0122] Place the sample to be tested on the table, level it, and measure its thickness data as required. Use non-woven fabric to wipe the measuring end face of the micrometer; press the measuring linkage mechanism to make the two measuring end faces completely contact, and press the "zero" key; the two measuring end faces of the micrometer are in contact with the end face of the sample to be tested, read the displayed data, and record the readings. Measure at intervals of 70mm perpendicular to the tape running direction (ie TD direction), and at intervals of 100mm along the tape running direction (ie MD direction); test 12 points along the TD direction of the sample to be tested; test 12 points along the MD direction of the sample to be tested; test a total of 24 points; take the average value of the thickness of the 24 points as the thickness of the sample to be tested.

[0123] The support layer is used as the sample to be tested, and the thickness H3 of the support layer is obtained.

[0124] The support layer and the lithium supplement layer are combined as the sample to be tested, and the total thickness H of the support layer and the lithium supplement layer is obtained. 支撑层&补锂 Layer; the total thickness of the support layer and the lithium supplement layer H 支撑层&补锂层 The difference between the thickness H3 of the support layer and the thickness H2 of the lithium supplement layer is H2, that is, H2 = H 支撑层&补锂层 -H3.

[0125] Tensile strength test of lithium supplement layer:

[0126] The steps for testing the tensile strength in the MD direction are as follows: the lithium supplement layer (including the support layer) is cut into standard test strips (width W = 16 mm, length L = 150 mm), wherein the width W of the standard test strip is along the TD direction, and the length L is along the MD direction. Use a tensile testing machine (model instron 3365), clamp both ends of the standard test strip in the upper and lower clamps of the tensile testing machine, center the standard test strip and do not fold or twist, apply tension at a constant speed of 50 mm / min until the standard test strip breaks, and record the load and corresponding extension. Calculate the tensile strength in the MD direction according to the following formula:

[0127] Tensile strength in MD direction = F1 / W; where F1 is the maximum load and W is the width of the standard test specimen.

[0128] First coulombic efficiency test:

[0129] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: charge the lithium-ion battery in the embodiment or comparative example at 25°C at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency is calculated according to the following formula.

[0130] First coulombic efficiency (%) = C1 / C0×100%.

[0131] Cycle performance test:

[0132] The voltage range marked on the factory battery packaging shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, the lithium-ion battery in the embodiment or comparative example is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, and then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the lithium-ion battery is measured to be A; then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the lithium-ion battery at the 400th time is measured to be B, and the cycle capacity retention rate is calculated according to the following formula.

[0133] Cycle capacity retention rate (%) = B / A × 100%.

[0134] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the lithium-ion battery.

[0135] Volume energy density test:

[0136] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, charge the lithium-ion battery in the embodiment or comparative example at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the lithium-ion battery 3 ) = length × width × height.

[0137] Volumetric energy density (Wh / L) = E / V × 10 6 .

[0138] Thermal safety performance test:

[0139] (1) At 25° C., the lithium ion battery in the embodiment or comparative example was charged at a constant current of 0.2 C to a cut-off voltage of 4.45 V, and then charged at a constant voltage of 4.45 V until the current was less than 0.05 C, and then allowed to stand for 5 min;

[0140] (2) Check the appearance of the lithium-ion battery and take photos before conducting the thermal safety performance test;

[0141] (3) Stick the temperature-sensing wire to the middle of the lithium-ion battery body;

[0142] (4) Place the lithium-ion battery vertically in the box, heat it to the target temperature (e.g., 135±2°C) at a heating rate of 5±2°C and maintain it for 60 minutes;

[0143] (5) Determine whether the lithium-ion battery catches fire or explodes and take photos;

[0144] (6) The highest temperature at which a lithium-ion battery does not catch fire or explode is the highest temperature that the lithium-ion battery can withstand, also known as the thermal safety passing temperature.

[0145] Example 1-1

[0146] <Preparation of negative electrode sheet>

[0147] The negative electrode active material silicon carbon material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 85:5:5:5, and deionized water is added as a negative electrode solvent, and the mixture is stirred and mixed to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%. The silicon carbon material is a silicon carbon composite material, and based on the mass of the silicon carbon composite material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%.

[0148] Adopt extrusion gap coating, and the negative electrode slurry is intermittently and evenly coated on the first surface of the negative electrode current collector copper foil with a thickness of 12μm along the running direction, and dried at 90°C to obtain a negative electrode sheet with a single-sided gap coating of the negative electrode material layer. Among them, along the running direction of the negative electrode sheet, the shortest distance D1 between two adjacent negative electrode material layer areas on the first surface is 20mm, and the length of a single negative electrode material layer area on the first surface is 1000mm. Then repeat the above steps on the second surface of the copper foil to obtain a negative electrode sheet with a double-sided gap coating of the negative electrode material layer. Among them, along the running direction of the negative electrode sheet, the shortest distance D2 between two adjacent negative electrode material layer areas on the second surface is 80mm, and the length of a single negative electrode material layer area on the second surface is 940mm. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting and slitting, a negative electrode sheet with a specification of 80mm×1020mm is obtained. Among them, the surface density of the negative electrode material layer is 2.3mg / cm 2 The compaction density of the cold pressing process is 1.0g / cm 3 .

[0149] <Preparation of pre-lithiated negative electrode sheet>

[0150] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled to a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer, and the roller pressure p12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure. The thickness H2 of the lithium supplement layer was 0.03mm.

[0151] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed in a weight ratio of 3:1:3:3 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.

[0152] After mixing the polymer polyvinylidene fluoride and the inorganic ceramic alumina in a weight ratio of 9:1, NMP is added as a solvent and mixed evenly to obtain an isolation membrane coating slurry with a solid content of 12wt%. The isolation membrane coating slurry is coated on one surface of a polypropylene (PP) base film with a thickness of 5μm along the tape running direction by extrusion gap coating (the second area is coated with the isolation membrane coating, and the first area is not coated with the isolation membrane coating), and dried to obtain a single-sided gap coated isolation membrane. Among them, along the tape running direction of the isolation membrane, the shortest distance D3 between two adjacent first areas is 20mm, and the length of a single first area is 1000mm. Then repeat the above steps on the other surface of the base membrane to obtain the first isolation membrane. The ionic conductivity σ11 of the first isolation membrane in the first area is 3mS / cm, the porosity P11 of the first isolation membrane in the first area is 40%, and the air permeability G2 of the first isolation membrane in the first area is 8s / 100mL. The ionic conductivity σ21 of the first isolation membrane in the second region is 0.05 mS / cm, and the porosity P21 of the first isolation membrane in the second region is 0.5%. The elongation of the first isolation membrane under a tensile force of 2 N / 10 mm is 1%, and the tensile strength of the first isolation membrane along the running direction is 5500 kg / cm 2 The thickness of the isolation film coating is 10 μm. The surface density of the isolation film coating is 12 mg / 5000 mm 2 .

[0153] The first isolation membrane is immersed in the electrolyte to obtain a first isolation membrane pre-impregnated with the electrolyte. The surface density CW1 of the electrolyte on the first isolation membrane pre-impregnated with the electrolyte is 20 g / mm 2 .

[0154] The first isolation film pre-impregnated with electrolyte is placed on the surface of the lithium replenishing layer to obtain a first lithium replenishing composite layer, which includes a support layer, a lithium replenishing layer and the first isolation film pre-impregnated with electrolyte, and the lithium replenishing layer is arranged between the first isolation film and the support layer. In the running direction of the lithium replenishing composite layer, the tensile strength K1 of the lithium replenishing layer (including the support layer) is 72N / 10mm.

[0155] After mixing the polymer polyvinylidene fluoride and the inorganic ceramic alumina in a weight ratio of 9:1, NMP is added as a solvent and mixed evenly to obtain an isolation membrane coating slurry with a solid content of 12wt%. The isolation membrane coating slurry is coated on one surface of a polypropylene (PP) base film with a thickness of 5μm along the tape running direction by extrusion gap coating (the second area is coated with the isolation membrane coating, and the first area is not coated with the isolation membrane coating), and dried to obtain a single-sided gap coated isolation membrane. Among them, along the tape running direction of the isolation membrane, the shortest distance D4 between two adjacent first areas is 80mm, and the length of a single first area is 940mm. Then repeat the above steps on the other surface of the base membrane to obtain a second isolation membrane. The ionic conductivity σ12 of the second isolation membrane in the first area is 3mS / cm, the porosity P12 of the second isolation membrane in the first area is 40%, and the air permeability G3 of the second isolation membrane in the first area is 8s / 100mL. The ionic conductivity σ22 of the second isolation membrane in the second region is 0.05 mS / cm, the porosity P22 of the second isolation membrane in the second region is 0.5%, the elongation of the second isolation membrane under a tensile force of 2 N / 10 mm is 1%, and the tensile strength of the second isolation membrane along the running direction is 5500 kg / cm 2 The thickness of the isolation film coating is 10 μm. The surface density of the isolation film coating is 12 mg / 5000 mm 2 .

[0156] The second isolation membrane is immersed in the electrolyte to obtain a second isolation membrane pre-impregnated with the electrolyte. The surface density CW2 of the electrolyte on the second isolation membrane pre-impregnated with the electrolyte is 20 g / mm 2 .

[0157] The second isolation membrane pre-impregnated with electrolyte is placed on the surface of the lithium replenishing layer to obtain a second lithium replenishing composite layer, which includes a supporting layer, a lithium replenishing layer and a second isolation membrane pre-impregnated with electrolyte, and the lithium replenishing layer is arranged between the second isolation membrane and the supporting layer.

[0158] The first lithium replenishing composite layer and the negative electrode plate are laminated so that the first isolation film contacts the negative electrode material layer on the first surface. The lamination method is pressing into a sheet. The first area is arranged opposite to the negative electrode material layer area, and the second area is arranged opposite to the empty foil area. The interface pressure p2 per unit area between the first lithium replenishing composite layer and the negative electrode plate is 0.4 MPa. The first lithium replenishing composite layer and the negative electrode plate are discharged through a voltage control system. The positive electrode of the voltage control system is connected to the negative electrode plate, and the negative electrode of the voltage control system is connected to the lithium replenishing layer of the first lithium replenishing composite layer. The constant current discharge current I1 of the discharge treatment is 1C, the discharge time t1 is 0.2h, and the temperature T1 of the discharge treatment is 55°C. At the same time, the second lithium replenishing composite layer and the negative electrode plate are laminated so that the second isolation membrane contacts the negative electrode material layer on the second surface. The lamination method is pressing into a sheet. The first area is arranged opposite to the negative electrode material layer area, and the second area is arranged opposite to the empty foil area. The interface pressure p3 per unit area between the second lithium replenishing composite layer and the negative electrode plate is 0.4MPa. The second lithium replenishing composite layer and the negative electrode plate are discharged through the voltage control system. The positive electrode of the voltage control system is connected to the negative electrode plate, and the negative electrode of the voltage control system is connected to the lithium replenishing layer of the second lithium replenishing composite layer. The constant current discharge current I2 of the discharge treatment is 1C, the discharge time t2 is 0.2h, and the temperature T2 of the discharge treatment is 55°C.

[0159] After the discharge treatment is completed, the first lithium replenishing composite layer, the second lithium replenishing composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate.

[0160] <Preparation of positive electrode sheet>

[0161] After mixing the positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added as the positive electrode solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 77mm×1015mm is obtained. Among them, the surface density of the positive electrode material layer is 19.0mg / cm 2 The compaction density of the cold pressing process is 4.15g / cm 3 .

[0162] <Preparation of electrolyte in lithium-ion batteries>

[0163] The electrolyte pre-impregnated with the isolation membrane in the lithium-supplementing composite layer is used as the electrolyte in the lithium-ion battery.

[0164] <Preparation of Separator Film in Lithium-ion Batteries>

[0165] A porous polypropylene film with a thickness of 5 μm (provided by Celgard Company) was used as the isolation membrane.

[0166] <Preparation of lithium-ion batteries>

[0167] The prepared positive electrode sheet, separator, pre-lithiated negative electrode sheet, and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the pre-lithiated negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.

[0168] Example 1-2

[0169] Except for adjusting the relevant preparation parameters according to Table 1 and Table 2, and the specifications of the negative electrode sheet in <Preparation of Negative Electrode Sheet> are 80mm×1005mm, and the specifications of the positive electrode sheet in <Preparation of Positive Electrode Sheet> are 77mm×1000mm, the rest is the same as Example 1-1.

[0170] Examples 1-3

[0171] Except for adjusting the relevant preparation parameters according to Table 1 and Table 2, and the specifications of the negative electrode sheet in <Preparation of Negative Electrode Sheet> are 80mm×1030mm, and the specifications of the positive electrode sheet in <Preparation of Positive Electrode Sheet> are 77mm×1025mm, the rest is the same as Example 1-1.

[0172] Example 1-4 to Example 1-7

[0173] Except that the porosity and air permeability of the separator in the first region are adjusted so that the ion conductivity of the separator in the first region is as shown in Table 1 and Table 2, the rest is the same as Example 1-1.

[0174] Example 1-8 to Example 1-10

[0175] Except that the porosity of the separator in the second region is adjusted so that the ion conductivity of the separator in the second region is as shown in Table 1 and Table 2, the rest is the same as Example 1-1.

[0176] Example 1-11 to Example 1-16

[0177] Except that the immersion time of the separator in the electrolyte is adjusted so that the surface density of the electrolyte on the separator pre-impregnated with the electrolyte is as shown in Table 1 and Table 2, the rest is the same as Example 1-1.

[0178] Example 1-17 to Example 1-27

[0179] Except for adjusting the relevant preparation parameters according to Table 1 and Table 2, the rest is the same as Example 1-1.

[0180] Example 2-1

[0181] Except for preparing the negative electrode sheet and the positive electrode sheet according to the following method, the rest is the same as Example 1-1.

[0182] <Preparation of negative electrode sheet>

[0183] Take the negative electrode slurry in Example 1-1, and use extrusion gap coating to intermittently and evenly coat the negative electrode slurry on one surface of a negative electrode current collector copper foil with a thickness of 12 μm in a direction perpendicular to the tape running direction, and dry at 90°C to obtain a negative electrode pole piece with a single-sided gap coating of a negative electrode material layer. Among them, along the tape running direction perpendicular to the negative electrode pole piece, the shortest distance D5 between two adjacent negative electrode material layer areas is 50 mm, and the width of a single negative electrode material layer area is 80 mm. Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode pole piece with a double-sided gap coating of a negative electrode material layer. Dry under vacuum conditions at 90°C for 1 hour, and then after cold pressing, cutting, and slitting, a negative electrode pole piece with a specification of 80 mm×1020 mm is obtained. Among them, the surface density of the negative electrode material layer is 2.3 mg / cm 2 The compaction density of the cold pressing process is 1.0g / cm 3 .

[0184] <Preparation of pre-lithiated negative electrode sheet>

[0185] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled to a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer, and the roller pressure p12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure. The thickness H2 of the lithium supplement layer was 0.03mm.

[0186] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed in a weight ratio of 3:1:3:3 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.

[0187] After mixing the polymer polyvinylidene fluoride and the inorganic ceramic alumina in a weight ratio of 9:1, NMP is added as a solvent and mixed evenly to obtain an isolation membrane coating slurry with a solid content of 12wt%. The isolation membrane coating slurry is coated on one surface of a polypropylene (PP) base film with a thickness of 5μm (the second area is coated with the isolation membrane coating, and the first area is not coated with the isolation membrane coating) in a direction perpendicular to the tape running direction, and dried to obtain a single-sided gap coated isolation membrane. Among them, along the tape running direction perpendicular to the isolation membrane, the shortest distance D6 between two adjacent first areas is 50mm, and the width of a single first area is 80mm. Then repeat the above steps on the other surface of the base membrane to obtain a third isolation membrane. The ionic conductivity σ13 of the third isolation membrane in the first area is 3mS / cm, the porosity P13 of the third isolation membrane in the first area is 40%, and the air permeability G4 of the third isolation membrane in the first area is 8s / 100mL. The ionic conductivity σ23 of the third isolation membrane in the second region is 0.05 mS / cm, the porosity P23 of the third isolation membrane in the second region is 0.5%, the elongation of the third isolation membrane under a tensile force of 2 N / 10 mm is 1%, and the tensile strength of the third isolation membrane along the running direction is 5500 kg / cm 2 The thickness of the isolation film coating is 10 μm. The surface density of the isolation film coating is 12 mg / 5000 mm 2 .

[0188] The third isolation membrane is immersed in the electrolyte to obtain a third isolation membrane pre-impregnated with electrolyte. The surface density CW3 of the electrolyte on the third isolation membrane pre-impregnated with electrolyte is 20 g / mm 2 .

[0189] The third separator pre-impregnated with electrolyte is placed on the surface of the lithium replenishing layer to obtain a third lithium replenishing composite layer, which includes a support layer, a lithium replenishing layer and a third separator pre-impregnated with electrolyte. The lithium replenishing layer is arranged between the third separator and the support layer.

[0190] The third lithium replenishing composite layer and the negative electrode sheet are laminated, so that the third isolation film contacts the negative electrode material layer on one surface, the first area is arranged opposite to the negative electrode material layer area, and the second area is arranged opposite to the empty foil area; the lamination method is to press into sheets, the interface pressure per unit area p4 between the third lithium replenishing composite layer and the negative electrode sheet is 0.4MPa, and the third lithium replenishing composite layer and the negative electrode sheet are discharged through the voltage control system, the positive electrode of the voltage control system is connected to the negative electrode sheet, and the negative electrode of the voltage control system is connected to the lithium replenishing layer of the third lithium replenishing composite layer, the constant current discharge current I3 of the discharge treatment is 1C, the discharge time t3 is 0.2h, and the temperature T3 of the discharge treatment is 55°C. At the same time, the negative electrode material layer on the other surface is pre-lithiated according to the above steps.

[0191] After the discharge treatment is completed, the third lithium supplement composite layer is peeled off from the negative electrode plate to obtain a pre-lithiated negative electrode plate.

[0192] <Preparation of positive electrode sheet>

[0193] After mixing the positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added as the positive electrode solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 77mm×1015mm is obtained. Among them, the surface density of the positive electrode material layer is 19.0mg / cm 2 The compaction density of the cold pressing process is 4.15g / cm 3 .

[0194] Example 2-2 to Example 2-4

[0195] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 2-1.

[0196] Example 3-1 to Example 3-10

[0197] Except for adjusting the relevant preparation parameters according to Table 4, the rest is the same as Example 1-1.

[0198] Comparative Examples 1 to 6

[0199] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0200] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 4.

[0201]

[0202]

[0203]

[0204] From Examples 1-1 to 1-27 and Comparative Examples 1 to 6, it can be seen that the lithium replenishment method provided in the present application is used to prepare a pre-lithiated negative electrode sheet, and the obtained pre-lithiated negative electrode sheet is applied to a lithium-ion battery. The prepared lithium-ion battery has a high thermal safety pass temperature, first coulomb efficiency, cycle capacity retention rate, and volume energy density, indicating that the safety performance and first coulomb efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved. In Comparative Examples 1 to 6, the lithium replenishment method is not within the scope of the present application, and the prepared lithium-ion battery has a low thermal safety pass temperature, first coulomb efficiency, cycle capacity retention rate, and volume energy density.

[0205] The structure of the negative electrode plate and the separator usually affects the safety performance and volume energy density of the lithium-ion battery. From Examples 1-1 to 1-3, it can be seen that the structure of the negative electrode plate and the separator is within the scope of this application, and the prepared lithium-ion battery has a high thermal safety pass temperature, first coulomb efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance and volume energy density of the lithium-ion battery can be improved, and the lithium-ion battery has a high first coulomb efficiency and a low cycle capacity attenuation.

[0206] The ionic conductivity of the separator in the first region usually affects the safety performance, first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-4 to 1-7 that the ionic conductivity of the separator in the first region is within the scope of the present application, and the prepared lithium-ion battery has a high thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance and first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved.

[0207] The ionic conductivity of the separator in the second region usually affects the safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-8 to 1-10 that the ionic conductivity of the separator in the second region is within the scope of the present application, and the prepared lithium-ion battery has a high thermal safety pass temperature, first coulomb efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance of the lithium-ion battery can be improved, and the lithium-ion battery has a high first coulomb efficiency, a low cycle capacity attenuation and a high volume energy density.

[0208] The surface density of the electrolyte on the separator of the pre-impregnated electrolyte usually affects the safety performance, first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-11 to 1-16 that the surface density of the electrolyte on the separator of the pre-impregnated electrolyte is within the scope of the present application, and the prepared lithium-ion battery has a higher thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance and first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved.

[0209] The interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode piece usually affects the first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-17 to 1-20 that the interface pressure per unit area between the lithium-replenishing composite layer and the negative electrode piece is within the scope of this application, and the prepared lithium-ion battery has a higher thermal safety passing temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved. At the same time, the lithium-ion battery also has good safety performance.

[0210] The temperature of the discharge treatment usually affects the safety performance, first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Examples 1-1, 1-25 to 1-27 that the temperature of the discharge treatment is within the scope of the present application, and the prepared lithium-ion battery has a higher thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance and first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved.

[0211] Table 3

[0212]

[0213] The structure of the negative electrode plate and the separator usually affects the safety performance and volume energy density of the lithium-ion battery. From Example 2-1 to Example 2-4, it can be seen that the structure of the negative electrode plate and the separator is within the scope of this application, and the prepared lithium-ion battery has a high thermal safety pass temperature, first coulomb efficiency, cycle capacity retention rate and volume energy density, indicating that the safety performance and volume energy density of the lithium-ion battery can be improved, and the lithium-ion battery has a high first coulomb efficiency and a low cycle capacity attenuation.

[0214] Table 4

[0215]

[0216]

[0217] The thickness of the lithium replenishment layer usually affects the first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Example 1-1, Example 3-1 to Example 3-4 that the thickness of the lithium replenishment layer is within the scope of this application, and the prepared lithium-ion battery has a higher thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that it can improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the volume energy density of the lithium-ion battery. At the same time, the lithium-ion battery also has good safety performance. Among Example 1-1, Example 3-1 to Example 3-4, the lithium replenishment layer of Example 3-4 is thicker, which will affect the production efficiency of the lithium-ion battery.

[0218] The thickness of the support layer usually affects the first coulombic efficiency, cycle capacity retention rate and volume energy density of the lithium-ion battery. It can be seen from Examples 1-1, 3-5 to 3-8 that the thickness of the support layer is within the scope of this application, and the prepared lithium-ion battery has a higher thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved. At the same time, the lithium-ion battery also has good safety performance.

[0219] The type of support layer usually affects the first coulombic efficiency, cycle capacity retention rate and volume energy density of lithium-ion batteries. It can be seen from Examples 1-1, 3-9 and 3-10 that the type of support layer is within the scope of this application, and the prepared lithium-ion battery has a higher thermal safety pass temperature, first coulombic efficiency, cycle capacity retention rate and volume energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the volume energy density of the lithium-ion battery can be improved. At the same time, the lithium-ion battery also has good safety performance.

[0220] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0221] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0222] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A lithium supplementation method, comprising the following steps: Providing a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; Providing a lithium supplement composite layer, the lithium supplement composite layer comprising a support layer, a lithium supplement layer and a separator pre-impregnated with an electrolyte, the lithium supplement layer being arranged between the separator and the support layer; The lithium-replenishing composite layer and the negative electrode plate are laminated so that the isolation film contacts the negative electrode material layer, and the lithium-replenishing composite layer and the negative electrode plate are subjected to a discharge treatment, wherein the constant current discharge current I of the discharge treatment is 0.1C to 3C, and the discharge time t is 0.067h to 2h; After the discharge treatment is completed, the lithium supplement composite layer and the negative electrode plate are peeled off to obtain a pre-lithiated negative electrode plate.

2. The lithium supplementation method according to claim 1, wherein: The negative electrode plate is a gap structure, and the gap structure includes a gap structure along the tape running direction or a gap structure perpendicular to the tape running direction.

3. The lithium supplementation method according to claim 2, wherein: When the negative electrode sheet is a gap structure along the running direction, along the thickness direction of the negative electrode sheet, the negative electrode current collector includes a first surface and a second surface opposite to each other; The first surface and the second surface are both provided with negative electrode material layer areas and empty foil areas in between; Along the running direction of the negative electrode sheet, the shortest distance D1 between two adjacent negative electrode material layer regions on the first surface is 5 mm to 30 mm, and the shortest distance D2 between two adjacent negative electrode material layer regions on the second surface is 30 mm to 150 mm.

4. The lithium supplementation method according to claim 3, wherein: The isolation film includes a first isolation film and / or a second isolation film, and the isolation film satisfies at least one of the following characteristics: (1) The first separator and the first surface are arranged opposite to each other, the first separator is a gap structure along the tape running direction, the first separator comprises a base film and a separator coating arranged on at least one surface of the base film, a first region and a second region are arranged on the surface of the base film, the second region is provided with a separator coating, the first region is arranged opposite to the negative electrode material layer region, and the second region is arranged opposite to the empty foil region; Along the running direction of the first isolation film, the shortest distance D3 between two adjacent first regions in the first isolation film is 5 mm to 30 mm; (2) the second separator and the second surface are arranged opposite to each other, the second separator is a gap structure along the tape running direction, the second separator comprises a base film and a separator coating arranged on at least one surface of the base film, a first region and a second region are arranged on the surface of the base film, the separator coating is arranged on the second region, the first region is arranged opposite to the negative electrode material layer region, and the second region is arranged opposite to the empty foil region; Along the running direction of the second isolation film, the shortest distance D4 between two adjacent first regions in the second isolation film is 30 mm to 150 mm.

5. The lithium supplementation method according to claim 2, wherein: When the negative electrode plate is a gap structure perpendicular to the running direction, the surface of the negative electrode collector is spaced apart by a negative electrode material layer area and an empty foil area; along the running direction perpendicular to the negative electrode plate, the shortest distance D5 between two adjacent negative electrode material layer areas on the surface of any negative electrode collector is 5 mm to 150 mm.

6. The lithium supplementation method according to claim 5, wherein: The isolation film includes a third isolation film, and the third isolation film is a gap structure along a direction perpendicular to the tape running direction. The third isolation film includes a base film and an isolation film coating arranged on at least one surface of the base film. The surface of the base film is spaced apart by a first area and a second area, and the second area is provided with an isolation film coating. The first area is arranged opposite to the negative electrode material layer area, and the second area is arranged opposite to the empty foil area. Along the tape running direction perpendicular to the third isolation film, the shortest distance D6 between two adjacent first areas on the surface of any base film is 5 mm to 150 mm.

7. The lithium supplementation method according to claim 4 or 6, which satisfies at least one of the following characteristics: (1) The ionic conductivity σ1 of the isolation membrane in the first region is 0.1 mS / cm to 5 mS / cm; (2) The porosity P1 of the isolation membrane in the first region is 30% to 45%; (3) The air permeability G of the separator in the first region is 6 s / 100 mL to 9 s / 100 mL.

8. The lithium supplementation method according to claim 4 or 6, which satisfies at least one of the following characteristics: (1) The ionic conductivity σ2 of the isolation membrane in the second region is 0 mS / cm to 0.1 mS / cm; (2) The porosity P2 of the separator in the second region is 0 to 1%.

9. The lithium supplementation method according to claim 1, wherein: The interface pressure p per unit area between the lithium supplementing composite layer and the negative electrode plate is 0.1 MPa to 0.6 MPa.

10. The lithium supplementation method according to claim 1, wherein: The temperature T of the discharge treatment is 25°C to 90°C.

11. The lithium supplementation method according to claim 1, which satisfies at least one of the following characteristics: (1) The surface density CW of the electrolyte on the separator of the pre-immersion electrolyte is 3 g / mm 2 Up to 60g / mm 2 ; (2) The thickness H2 of the lithium replenishing layer is 0.001 mm to 1 mm; (3) The thickness H3 of the support layer is 3 μm to 50 μm; (4) The support layer comprises at least one of copper foil, nickel foil, steel foil or copper-nickel alloy foil; (5) Along the running direction of the lithium-replenishing composite layer, the tensile strength K1 of the lithium-replenishing layer is 0.5 N / 10 mm to 200 N / 10 mm.

12. The lithium supplementation method according to claim 1, which satisfies at least one of the following characteristics: (1) The surface density CW of the electrolyte on the separator of the pre-immersion electrolyte is 5 g / mm 2 Up to 30g / mm 2 ; (2) The thickness H2 of the lithium replenishing layer is 0.005 mm to 0.1 mm; (3) The thickness H3 of the support layer is 5 μm to 20 μm; (4) Along the running direction of the lithium-replenishing composite layer, the tensile strength K1 of the lithium-replenishing layer is 1 N / 10 mm to 100 N / 10 mm.

13. A pre-lithiated negative electrode sheet prepared by the lithium replenishment method according to any one of claims 1 to 12. 14 . A secondary battery comprising the pre-lithiated negative electrode sheet according to claim 13 . 15 . An electronic device comprising the secondary battery according to claim 14 .

Citation Information

Patent Citations

  • Preparation method of negative electrode pre-lithiated lithium ion battery, and negative electrode pre-lithiated lithium ion battery

    CN112786971A

  • Electrochemical device, electronic device and method for preparing negative pole piece

    CN116097472A

  • Lithium pre-supplementing negative pole piece and preparation method thereof, secondary battery and electronic device

    CN117096472A